Analysis Of Perforated Piezoelectric Sandwich Smart Structure Cantilever Beam Using COMSOL. (2018) - Sivakumar, N.; Kanagasabapathy, H.; Srikanth, H.P.
Abstract: This paper addresses the analysis of smart structure to implement a cantilever beam using COMSOL. The model of the smart structure is geometrically defined and developed using finite element method with meshing in various stages. 3D static bending of a beam due to applied loading and electrostatic forces together couple so as to optimally generate electric potential distribution for a specified region which facilitates thereby for the plotting of curves to be studied in this paper. The details of the meshing reveal a definite range of voltage and applicable load to make significant displacement of the beam.